Development and Investigation of a NASICON‐Type High‐Voltage Cathode Material for High‐Power Sodium‐Ion Batteries. (3rd January 2020) - Chen, Mingzhe; Hua, Weibo; Xiao, Jin; Cortie, David; Guo, Xiaodong; Wang, Enhui; Gu, Qinfen; Hu, Zhe; Indris, Sylvio; Wang, Xiao‐Lin; Chou, Shu‐Lei; Dou, Shi‐Xue
Abstract: Herein, we introduce a 4.0 V class high‐voltage cathode material with a newly recognized sodium superionic conductor (NASICON)‐type structure with cubic symmetry (space group P 21 3), Na3 V(PO3 )3 N. We synthesize an N‐doped graphene oxide‐wrapped Na3 V(PO3 )3 N composite with a uniform carbon coating layer, which shows excellent rate performance and outstanding cycling stability. Its air/water stability and all‐climate performance were carefully investigated. A near‐zero volume change (ca. 0.40 %) was observed for the first time based on in situ synchrotron X‐ray diffraction, and the in situ X‐ray absorption spectra revealed the V 3.2+ /V 4.2+ redox reaction with high reversibility. Its 3D sodium diffusion pathways were demonstrated with distinctive low energy barriers. Our results indicate that this high‐voltage NASICON‐type Na3 V(PO3 )3 N composite is a competitive cathode material for sodium‐ion batteries and will receive more attention and studies in the future. Abstract : Ein neues Kathodenmaterial vom NASICON‐Typ aus Na3 V(PO3 )3 N wurde synthetisiert und durch Kombination mit einer Kohlenstoffmatrix in seiner elektrochemischen Leistung verbessert. Das Material wurde mit In‐situ‐XAS und ‐XRD untersucht, und die 3D‐Natriumdiffusionswege wurden mithilfe von Dichtefunktionalrechnungen eindeutig identifiziert.